Effects of Anthocyanin Extracts from Bilberry (Vaccinium myrtillus L.) and Purple Potato (Solanum tuberosum L. var. ‘Synkeä Sakari’)on the Plasma Metabolomic Profile of Zucker Diabetic Fatty Rats - Kang Chen; Xuetao Wei; Jian Zhang; Raghunath Pariyani; Johanna Jokioja; Maaria Kortesniemi; Kaisa M. Linderborg; Jari Heinonen; Tuomo Sainio; Yumei Zhang; Baoru Yang (American Chemical Society, 2022)
This study compared the effects of the nonacylated and acylated anthocyanin-rich extracts on plasma metabolic profiles of Zucker diabetic fatty rats. The rats were fed with the nonacylated anthocyanin extract from bilberries (NAAB) or the acylated anthocyanin extract from purple potatoes (AAPP) at daily doses of 25 and 50 mg/kg body weight for 8 weeks. 1H NMR metabolomics was used to study the changes in plasma metabolites. A reduced fasting plasma glucose level was seen in all anthocyanin-fed groups, especially in the groups fed with NAAB. Both NAAB and AAPP decreased the levels of branched-chain amino acids and improved lipid profiles. AAPP increased the glutamine/glutamate ratio and decreased the levels of glycerol and metabolites involved in glycolysis, suggesting improved insulin sensitivity, gluconeogenesis, and glycolysis. AAPP decreased the hepatic TBC1D1 and G6PC messenger RNA level, suggesting regulation of gluconeogenesis and lipogenesis. This study indicated that AAPP and NAAB affected the plasma metabolic profile of diabetic rats differently.